Reconnecting through Urban Agriculture: A community-engaged video ethnography in Winnipeg - Bowness, Evan; Baird, Natalie; Hallberg, Avery; Packulak, Mark (Engaged Scholar Journal, 2020)
While contemporary urban life in many ways seems increasingly disconnected from nature, the growing practice of urban agriculture – growing food in and around cities – is increasingly pointed to as a source of well-being through a connection to the land. In addition to providing access to healthy food and providing a means for increased physical activity, urban agriculture boasts a number of subjective positive experiences for participants. Reporting from an intensive, community-based ethnographic research project in Winnipeg, Manitoba, students and course organizers of the University of Manitoba’s “Applied Visual Methods in Community-Based Sociology” course explored urban agriculture as a source of well-being through the lens of disconnection and reconnection. During the summer course, eight students from different disciplinary backgrounds conducted participatory observation and interviews in five community garden sites. The results of the research were developed in a group paper and presented in a short video. This report from the field shares the methodology of short-term ethnographic video as a means of both engaged scholarship through the principle of reciprocity and as a vehicle for exploring urban agriculture (and other food movement activities) as a pathway to well-being by reconnecting to land, to food and to community.